Fast scintillating Ce3+ doped gadolinium aluminum fluoroborate glass for calorimetry in proton CT prototype: A preliminary work. (April 2023) - Boontueng, P.; Ritjoho, N.; Wantana, N.; Limkitjaroenporn, P.; Kim, H.J.; Sanghangthum, T.; Chanlek, N.; Limphirat, A.; Yan, Y.; Kaewkhao, J.; Kobdaj, C.
Abstract: In this work, Ce 3+ -doped gadolinium aluminum fluoroborate glass scintillators, 25Gd2 O3 -(65-x)B2 O3 –10AlF3 -xCeF3, where, x = 0, 0.05, 0.1, 0.2, and, 0.3 mol%, were prepared and studied systematically for developing a proton calorimeter used in proton-computed tomography. Various properties of the prepared glass scintillators were evaluated through density, X-ray absorption near edge spectroscopy, transmittance, photoluminescence, decay time, X-ray-induced luminescence, and proton-induced luminescence measurements. The highest density of the fabricated glass scintillators reached 4.31 g/cm 3 . The X-ray-induced luminescence showed a broad emission band centered at approximately 400 nm, and the decay time was less than 30 ns. The glass scintillators were irradiated by a proton beam with a beam energy of 100–115 MeV. It was found that the glass scintillators emitted light at almost the same wavelength as that of the X-ray-induced luminescence. Moreover, the energy deposition inside the fabricated glass scintillators was simulated using GATE simulation and compared with the results obtained for proton-induced luminescence. The energy deposition obtained from the simulation showed the same trend as that for the fraction of light emitted from the proton irradiation measurement. Therefore, these fabricated glass scintillators can be used as calorimeter in medical physics and other applications related to proton or X-ray irradiation. Highlights: Fabrication of Ce3+ doped gadolinium aluminum fluoroborate glass scintillators. Study of scintillation properties via variations in cerium concentration. Fabricated scintillators had high density (max. 4.31 g/cm 3 ) and fast decay (<30 ns) Photoluminescence spectra, broad X-ray-induced luminescence, and proton irradiation. GATE simulated energy deposition has same trend as proton irradiation measurements.